Revealing insights of users' perception: an approach to evaluate wearable products based on emotions. (3rd July 2020) - Liao, Ting; Tanner, Kesler; MacDonald, Erin Faith
Abstract : The wearable product market is growing rapidly and is full of products with similar functions and features. Engaging users at an emotional level may be the key to differentiating a product and encouraging long-term use. While researchers have proposed various design approaches to realize design qualities for wearable devices, emotional needs are often extracted by analysis-heavy methods and disconnected in the design process. To bridge this gap, we developed a new approach that uses a two-axis interactive collage tool for users to compare and evaluate wearable products with targeted emotion-related descriptive words. This approach enabled designers to explore how users perceive products and identify types of emotions that were associated with users' preferences for and perception of the product's form and visible characteristics. The example study demonstrated this approach by exploring the relationships between product characteristics and design goals, such as user comfort, user delight, and perceived product usefulness. The results showed that products that resemble clothing were perceived as more delightful and comfortable. The approach can be further used to explore other design concepts or goals.